SIKAP MASYARAKAT LOKAL TERHADAP KONSERVASI DAN TAMAN NASIONAL SEBAGAI PENDUKUNG KEPUTUSAN DALAM PENGELOLAAN TAMAN NASIONAL KERINCI SEBLAT (STUDI KASUS DI KABUPATEN KERINCI DAN LEBONG, INDONESIA) - Teguh Adiprasetyo; Eriyatno Eriyatno; Erliza Noor; Fadjar Sofyar (Environmental Research Center (PPLH) of Udayana University, 2009)
The number of national parks in Indonesia increased rapidly since 1982. Support from local people plays an important role in sustaining national parks, therefore their needs, aspirations and attitudes should be considered to assure better national park management. This research was intended to discern the knowledge, perception and attitude of local people residing close to Kerinci Seblat National Park towards the park and its conservation initiatives, to identify factors affecting them, and to determine if local communities perceived more benefit from the park were likely to support it. Knowledge of local people about the existence of the park and regulation governed it was high. However, knowledge of local people about its function and benefit for society was relatively low. Attitudes of local people on the park and its conservation initiatives was affected by many factors including their involvement in an organization, administrative residence affiliation (district), ethnic, formal education attainment, distance of residence to national park, income, family size, affluence, and agricultural land ownership. Almost all of the local people perceived that the park did not give them economic benefit directly, therefore they expected to be involved in planning and making use of it. They also perceived that it was needed to conserve natural resources and supply ecological services. However, most of the people perceived that their lives did not depend on the park, so its existence should not be guarded collectively.